Disturbing the neighbours: an investigation into the relationship between psychopathology and social formations - Collins, Anthony (Rhodes University, Faculty of Humanities, Department of Psychology, 1995)
This work attempts to confront certain political problems created by the individualistic bias in psychoanalytic thinking, and the resulting failure to adequately theorise the importance of social processes. The thesis traces the origins of intrapsychic thinking to Freud's initial move from the seduction theory to the Oedipal theory. This development is offered as a prototype for the debates between conceptualisations of childhood traumatisation as a social problem of actual abuse occurring within dermed power relations, and theories which locate pathology purely within internal conflicts occurring inside the individual. Several criticisms of this shift are offered, and it s impact on later theory is considered. Here a contrast is offered between the theoretical approaches of Melanie Klein and Donald Winnicott, arguing for the usefulness of Winnicott's emphasis on environmental factors within psychodynamic theory. The impact of these theoretical approaches is illustrated through a critical evaluation of Freud's case study of Judge Schreber. Additional historical material is brought in to show the importance of environmental considerations ignored by Freud, and contrasting psychodynamic readings of the case are offered. As an alternative to purely intrapsychic approaches, a reinterpretation of certain strands of Critical Theory is then presented. Adorno's theory of the Authoritarian Personality and Marcuse' s concept of One-Dimensional Man are extended using Winnicott's formulations concerning psychological development. This leads to an examination of the question of the relationship between social structure and individual consciousness. Post-structuralist accounts of language and the construction of identity are explored. These are then developed drawing on theories of ideology, language and consciousness, integrating these with Winnicott's developmental theory to offer an alternative psychodynamic understanding of the relationship between social process and psychopathology. An attempt is made to reformulate - the notions of consciousness and the unconscious in terms of the possibilities and difficulties of representation within available social symbolic codes. In conclusion the it is argued that psychology needs to integrate critical social theory and contemporary understandings of the social construction of consciousness in order to become a meaning force in positive social transformation.
Keywords: Freud, Sigmund, 1856-1939; Winnicott, D. W. (Donald Woods), 1896-1971; Social psychiatry; Social psychology; Psychology, Pathological; Frankfurt school of sociology; Political psychology